Evaluasi Tubes Plugging terhadap Kinerja Kondensor PLTU Adipala - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Arash (JTM : JURNAL TEKNIK MESIN, 2026)
This study evaluates the effect of tubes plugging on the condenser performance of Unit 1 at PLTU Adipala 1x660 MW. The analysis used operating data before plugging on 26 October 2017, 26 October 2018, and 29 November 2018, and after plugging on 29 October 2017, 2 November 2018, and 9 February 2019. Condenser performance was assessed using logarithmic mean temperature difference (LMTD), temperature rise (TR), heat-transfer area, heat load, and overall heat-transfer coefficient (U). The results show that after the third plugging condition, LMTD decreased to 7.413 °C in condenser A and 8.145 °C in condenser B, while TR decreased to 9.855 °C and 8.716 °C, respectively. Although U increased to 29.893 kW/m².°C in condenser A and 23.732 kW/m².°C in condenser B, the increase was associated with higher cooling-water flow demand and reduced active heat-transfer area. The findings indicate that tubes plugging is effective as short-term leakage mitigation, but increasing plug quantity reduces condenser heat-transfer capacity and requires monitoring of cooling-water flow, fouling, and condenser vacuum.